A prospective comparative study of cesarean section in multiparous and primiparous women - DR. Y. ANUPAMA SURESH; DR. Y.V. SURESH (International Journal of Pharma and Bio Sciences, 2017)
To compare the indications for caesarean section in multipara and primipara, to compare the maternal morbidity and mortality, to study the incidence of perinatal mortality and to correlate the birth weight with multiparty.100 patients were selected at random for a thorough clinical study. The study was conducted for a period of 1 year i.e 2015-2016, in KMC Hospital Mangalore, Karnataka. The sample comprised of 50 cases of multiparous women undergoing caesarean section for the first time (30 cases grand multiparas and 20 cases of multiparas) 50 primigravida’s were included in the series for comparative study, the women admitted into the obstetric ward. Out of 208 deliveries the incidence of caesarean section is 48.4%. Most common age group is 26-30Yrs age group is multiparous women 16(32%) cases and in primiparous are of age 20-25 yrs are 14(28%) cases . 11 case (22%) of multis had elective caesarean section compared to 28 cases (56%) of primis. 39 cases (78%) of multies had emergency caesarean section as compared to 22 cases (44%) of primis. Most of caesarean section in multiparous were performed for maternal indication. incidence of elective and emergency LSCS in multie and primies was found to be very highly significant (p=0.0005). Antepartum haemorrhage was principle indication for all caesarean section in 23 cases (grand multi-6cases, muliti-5 and primiparous 12 cases) (23%). Cephalopelvic disproportion is more common in primiparous women. Hypertension and anaemia were common in multiparous women. Preeclamptic toxaemia and anemia in primiparous women are common. 4 cases of cesarean section were done for foetal indications in multiparous women. There were 3 cases of foetal morbidity, 1 due to Respiratory Tract Infection, 1 had jaundice and 1 had umbilical sepsis. There was only one neonatal death due to accidental haemorrhage. Wound infection and urinary tract infection was common in multiparaous women. Sub involution of uterus was seen more in primigravidas. It can be concluded that women who had previous uneventful labours, may have different complications during subsequent pregnancy and due importance should be given to each pregnant mother.